Kebijakan Publik Deliberatif Pemerintahan Desa: Catatan Legal-Historis Selama Implementasi Otonomi Daerah - Ramda, Eduardo Edwin (Bestuurskunde: Journal of Governmental Studies, 2025)
Post-reform, the Indonesian government has guaranteed open access to public participation down to the village level through various legal products, ranging from laws to government regulations. However, behind this commitment, a phenomenon of pseudo-participation has emerged, revealing serious issues and challenges in its implementation. Existing regulations, which are supposed to govern the norms of public participation, often become “paper tigers”, they do not function optimally within the policy-making process. The gap between the ideal conditions outlined in the regulations and the reality on the ground becomes a crucial point, particularly because the deliberative process in formulating public policies at both central and regional levels remains very limited. This study uses a qualitative approach with a case study method in several villages that have implemented public participation mechanisms in development planning. The proposed solution is institutional strengthening through the establishment of village deliberative forums that are not merely ceremonial but have formal legitimacy and substantive capacity to influence the decision-making process. In addition, the role of non-state actors such as civil society organizations and local media is also strengthened as guardians of a critical and inclusive discourse space. The novelty of this study lies in its emphasis on the need for institutional pressure and coercion mechanisms to ensure that deliberative processes are consistently carried out. Thus, it is expected that policies will truly reflect the needs and aspirations of the citizens, especially in villages that have so far only been objects of policy, not subjects of policymaking.